Manajemen Perubahan Perspekttif Islam - Muhammad Syafuan Zairie (Jurnal Manajemen Kreatif dan Inovasi, 2023)
This research examines change management in an Islamic perspective. The research method used is a qualitative approach using literature studies and theoretical analysis. Through an in-depth understanding of related literature, concepts and principles of change management that are appropriate to the context of Islamic education are identified. In this study, data will be collected through literature studies which include books, journals, articles, and other reliable sources related to change management from an Islamic perspective. Change management is an effort made by a leader or manager in subordinating a plan, coordination, direction, control/supervision to achieve goals or objectives that can make an organization or institution better than yesterday to achieve goals. Change Management in Islamic perspective consists of phases namely human, development.